PENGKLASTERAN LAHAN SAWAH DI INDONESIA SEBAGAI EVALUASI KETERSEDIAAN PRODUKSI PANGAN MENGGUNAKAN FUZZY C-MEANS - Nur Afifah; Dian Candra Rini Novitasari; Ahmad Lubab (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2016)
The number of rice field in Indonesia is decreasing due to development of residential areas and buildings. Consequently, it reduces foodstuff availability and government should import it from other. Increasing food production and minimizing imported food can be started by clustering fields as an evaluation. This clustering is approached by Fuzzy C-Means. Training and Testing data are implemented on Matlab and yield three categories, wide, medium and narrow field. Moreover, the most potential field is East Java, Central Java, and West Java